Implementación de una celda electrolítica de agua para un prototipo de motor ciclo Otto, a fin de disminuir las emisiones de monóxido de carbono (CO) - Vera Franco, David Ricardo; Moreno Aya, Alvaro Alberto (Universidad Antonio Nariño, 2023)
This document proposes the implementation of an electrolytic water cell in a gasoline engine with a cylinder capacity of 163cc that allows evidence of the reduction of carbon monoxide generated by internal combustion engines that operate under the Otto cycle (4 times)